PENGARUH ARSITEKTUR KEUANGAN, CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PERBANKAN DI INDONESIA - Ni Ketut Karwini; I Nyoman Widhi Astawa (Forum Manajemen STIMI Handayani Denpasar, 2020)
This study aims to analyze and explain the influence of financial architecture dimension consisting of ownership structure, capital structure and corporate governance as well as adding another variable that is CSR to firm value. This study was conducted at banks listed in Indonesia Stock Exchange (IDX) period 2017 using secondary data source, consisting of 81 bank, of which 76 banks as a sample because it has complete data. The analysis method used is linear regression analysis, multiple correlation analysis, determination analysis and t test. The results showed that the financial architecture, capital structure, corporate governance and CSR have a positive and significant impact on firm value.